Red algae extract suppresses caspase-3 gene expression and induces catalase antioxidant enzyme in testicles of rats induced by boric acid - Ayu Renda Sari; Joko Wahyu Wibowo; Sri Priyantini; Agung Putra; Nur Dina Amalina (Medicinski glasnik, 2023)
Aim: To determine the effect of red algae extract on the gene expression of catalase and caspase-3 in testicules of rats induced by boric acid (BA). Methods: This is experimental research with post-test control group design. Twenty four healthy male Wistar rats were divided into four treatment groups: a healthy group, negative control group, two treatment groups with red algae extract 400mg/kgBW/day (T1) and red algae extract 800mg/kgBW/day (T2). Each group was treated with BA 500mg/kgBW/day for 14 days, whereas the healthy group did not receive BA. In the treatment groups T1 and T2 were given red algae extract for 14 days. On day 15 all treatment groups were terminated and catalase and caspase-3 gene expression were analysed using qRT-PCR. Results: In the healthy group, the expression of the catalase gene was 1.39±0.67 and the expression of the caspase-3 gene was 1.06±0.17. In the negative control group, there was a significant decrease in catalase gene expression, 0.68±0.27 (p<0.05), and a significant increase in caspase-3 gene expression, 5.71±2.47 (p<0.05). Treatment groups T1 and T2 showed a significant increase in catalase gene expression, 2.67±0.69; and 2.85±0.64, respectively (p<0.05) and caspase-3, 3.96±1,16 and 1.89±0.84, respectively, compared to the control group. Conclusion: The administration of red algae extract had a significant effect on increasing the expression of the catalase gene and decreasing the expression of the caspase-3 gene. This suggests that red algae extract has the potential to be developed as a protective agent against exposure to the effects of BA.
Keywords: boric acid; Caspase-3; catalase; red algae extract; testicular